The Role of the Aceullular Pertussis Vaccine and the Comeback of 'Pertussis Pete'? - John M Conly; B Lynn Johnston (Canadian Journal of Infectious Diseases)
Pertussis or whooping cough is an acute infectious disease of the respiratory tract caused principally by Bordetella pertussis and less commonly by Bordetella parapertussis (1). Until two decades ago, pertussis in adults was a medical curiosity (2-4), but with the purification of specific Bordetella species antigens, the development of reliable enzyme immunoassays allowing accurate serological diagnosis and better understanding of the duration of immunity from vaccination, it has been clearly demonstrated that B pertussis is a common cause of prolonged cough in adults. Indeed, its incidence has been increasing gradually over the past decade in both adults and adolescents. Given the recognition of the importance of pertussis as a cause of prolonged cough in adults and the advent of the new acellular pertussis vaccines, it is timely to review current concepts of the pathogenesis of pertussis, its epidemiology in adults and the utility of the anticipated impact of the acellular vaccine.